Liposome chaperon in cell-free membrane protein synthesis: one-step preparation of KcsA-integrated liposomes and electrophysiological analysis by the planar bilayer method. (9th November 2015) - Ando, M.; Akiyama, M.; Okuno, D.; Hirano, M.; Ide, T.; Sawada, S.; Sasaki, Y.; Akiyoshi, K.
Abstract : Chaperoning functions of liposomes were investigated using cell-free membrane protein synthesis. Abstract : Chaperoning functions of liposomes were investigated using cell-free membrane protein synthesis. KcsA potassium channel-reconstituted liposomes were prepared directly using cell-free protein synthesis. In the absence of liposomes, all synthesized KcsA protein aggregated. In the presence of liposomes, however, synthesized KcsA spontaneously integrated into the liposome membrane. The KscA-reconstituted liposomes were transferred to the planar bilayer across a small hole in a thin plastic sheet and the channel function of KcsA was examined. The original electrophysiological activities, such as voltage- and pH-dependence, were observed. These results suggested that in cell-free membrane protein synthesis, liposomes act as chaperones, preventing aggregation and assisting in folding and tetrameric formation, thereby allowing full channel activity.